PENGARUH PENGELOLAAN KEUANGAN DAERAH DAN KOMITMEN TERHADAP PENYUSUNAN LAPORAN KEUANGAN PADA PEMERINTAH DAERAH KOTA KENDARI - Husin, Husin; Mustafa, Santiadji; Safaa, Violla (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACT The research aims to know effect of financial management and commitment to the Financial Statements of Local Government Kendari. The hypothesis of this study is the financial management and commitment to significantly influence the financial statements of local government. The samples used were 27 respondents financial statement of local government team. The sampling technique with census sampling method. To answer the hypothesis is used analysis linear regression multiply combine with SPSS 20.T-test result shows that the partial financial management has t count 2.720 greater than t table 1.710 and commitment have t hitung 2.992 greater than t table. This shows that all independent variables a significant effect on the financial statements of local government. The coefficient of the regression results adjusted R Square of 0.739. This means that the variance of independent variables that explain 73.9% of the dependent variable, while the remaining 26.1% is explained by other variables not examined. The results of this study indicate that Financial Management has a significant impact on the Financial Statements of Local Government as well as the commitment to have a significant impact on the Financial Statements of Local Government. Keywords: Financial Management, Commitment, and Financial Statements of Local Government